eCM 2019
DOI: 10.22203/ecm.v037a10
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale secretome analyses unveil the superior immunosuppressive phenotype of umbilical cord stromal cells as compared to other adult mesenchymal stromal cells

Abstract: Mesenchymal stromal cells (MSCs), given their regenerative potential, are being investigated as a potential therapeutic tool for cartilage lesions. MSCs express several bioactive molecules which act in a paracrine fashion to modulate the tissue microenvironment. Yet, little is known about the divergence of these signalling molecules in different MSC populations. The present study investigated secretomes of stromal cells harvested from Hoffa's fat pad (HFPSCs), synovial membrane (SMSCs), umbilical cord (UCSCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…These data concur with previous studies that have consistently shown MSCs reduce apoptosis and increase proliferation of several cell types [29] . The authors saw no difference in microglial activation overall or regionally; given the key role of MSCs in immunomodulation [8] , this was surprising. As evolving damage from inflammation can last weeks to months, an effect on neuroinflammation from huMSCs may become more apparent in longer-term studies [31] .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These data concur with previous studies that have consistently shown MSCs reduce apoptosis and increase proliferation of several cell types [29] . The authors saw no difference in microglial activation overall or regionally; given the key role of MSCs in immunomodulation [8] , this was surprising. As evolving damage from inflammation can last weeks to months, an effect on neuroinflammation from huMSCs may become more apparent in longer-term studies [31] .…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the authors used huMSCs, which have superior anti-inflammatory effects compared with adult MSCs [8] . MSCs have the potential to treat adult diseases such as stroke [25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences involve a different presence of angiogenic factors [68], a lower amount of metalloproteinases (MMPs) [67,69], that could be potentially beneficial in counteracting cartilage hypertrophy and degradation but, also, a lower ECM protein content [69]. On the other hand, the higher production of TGF-β, chemokines and anti-inflammatory cytokines could make the wjMSCs' secretome a perfect candidate to control the inflammatory process [67][68][69][70]. Similarly, EVs and, in particular, exosomes isolated from both wjMSCs and cbMSCs exerted antifibrotic [71,72], antiapoptotic, proliferative [32,73] and immunomodulatory effects [73][74][75] through the delivery to the target cells of several biological factors, including nucleic acids and proteins and, in particular, cytokines [32,73].…”
Section: Secretome Of Cord Blood and Wharton's Jelly Msc For Oa And Rmentioning
confidence: 99%
“…One of the most important features is immunomodulative activity [ 1 , 2 ]. In the case of activation of the inflammatory process, MSCs indirectly interact with all types of cells of the immune system through the secretion of therapeutic factors that show antiapoptotic, angiogenic and immunosuppressive activity [ 3 , 4 ]. Moreover, the MSCs may also interact with the immune system via direct cell-cell contact with every type of immune system cell.…”
Section: Introductionmentioning
confidence: 99%